Effectiveness of Ceiling Cassette Air Conditioner Placement on Building Comfort and Energy Efficiency: A Systematic Literature Review - Dharma, Budi -; Siregar, Ahmad Marabdi (Rekayasa Material, Manufaktur dan Energi, 2026)
The installation location of ceiling cassette air conditioning units is a critical factor in Heating, Ventilation, and Air Conditioning (HVAC) system design, particularly in public service buildings where high thermal comfort and energy efficiency are essential. This study aims to systematically examine the influence of ceiling cassette air conditioner placement on airflow distribution, thermal comfort, and building energy performance through a Systematic Literature Review (SLR) approach. The review analyzes peer-reviewed, open-access scientific articles published between 2020 and 2025, selected using a structured and transparent literature screening protocol. The synthesis results indicate that improper unit placement can lead to uneven temperature distribution, increased thermal discomfort, and higher energy consumption. Conversely, strategic placement that accounts for room geometry, airflow orientation, and occupied zones consistently improves thermal uniformity and enhances HVAC energy efficiency. These findings highlight that ceiling cassette unit placement should be considered an integral component of HVAC design rather than a secondary technical decision. This study contributes to the existing body of knowledge by providing evidence-based insights that support more effective and sustainable HVAC design practices for both researchers and industry practitioners.